Ultrastructural description of Myxobolus cuneus (Myxosporea) in the skeletal muscle and kidney of tropical farmed fish Piaractus mesopotamicus (Characiformes: Characidae) - Manrique, Wilson Gomez; Pereira Figueiredo, Mayra Araguaia; Andrade Belo, Marco Antonio de [UNESP]; Martins, Mauricio Laterca; Azevedo, Carlos (Springer, 2016)
This study characterizes by transmission electron microscopy (TEM) and morphometric features the myxozoan Myxobolus cuneus (Myxosporea) in Piaractus mesopotamicus and reports the skeletal muscle and kidney as site of infection. The register was based in 21 young fish from intensive fish farming in Southeast Brazil and the spores were analyzed in fresh-mounted slides of the infected organs stained with Toluidine blue and processed as usual for TEM. It differs from Myxobolus cunhai from the fish host and different polar capsule size, and from Myxobolus serrasalmi on the pyriform spore shape and an oval macrospore, differently to that reported in this study. Morphometric characteristics and TEM study confirmed the present material as M. cuneus.
Keywords: Freshwater fish; Pacu; Myxozoa; Transmission electron microscopy